(3cJGH aj GdJhMjOs
(3ChdgG (B:s
(3CeG HYO abGd Hf Gdbje aj EYdGe GdehbYjf s
(3BNQgG (B:s
(3hefge ef ojYGTQ GdcdGH hGdMjGJ hge ebUQhf ajeG CeQ Gddg Hg QShdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3GdfSNI HgG MhGTs
(3hQOJ CjVkG JMJ Qbe (B13/430s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds